Pengaruh Pekerjaan, Promosi, Rekan Kerja, Atasan, Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Studi Kasus Di Pt. Primissima Medari Sleman Yogyakarta - Fx Pudjo Wibowo; Fidellis Wato Tholok (Sains: Jurnal Manajemen dan Bisnis, 2019)
The purpose of this paper is to determine the extent of the influence of work, promotion, co-workers, superiors and work environment on employee work productivity at PT. PRIMISSIMA MEDARI SLEMAN Yogyakarta. Validity and reliability tests show that all question items are from work variables (X_1), promotions (X_2), coworkers (X_3), supervisors (X_4) and work environment (X_5), all valid and reliable questions, t value calculated jobs 1.987 , the value of promotion t count is 2.326, the value of the worker's t count is 4,870, the value of the t count of the boss is 7,597 and the value of the t count of work environment is 2,363 which all shows greater than t table 1,984, so this hypothesis states that work (X_1), promotion (X_2) , coworkers (X_3), superiors (X_4) and work environment (X_5) partially positive effect on employee work productivity at. PT. PRIMISSIMA MEDARI SLEMAN Yogyakarta. F count is 142,920 with a significance value of 0,000 so that the value of F count> F table or 142,920> 2.46 or the level of significance (sig) 0,000 <0.05, then it can be concluded that simultaneously (together) between work (X_1), promotion (X_2 ), coworkers (X_3), superiors (X_4) and work environment (X_5), towards work productivity of employees at PT. PRIMISSIMA MEDARI SLEMAN Yogyakarta and the results of the coefficient of determination show that work (X_1), promotion (X_2), coworkers (X_3), boss (X_4) and work environment (X_5) contribute 88, 4% to Employee Productivity at PT. PRIMISSIMA MEDARI SLEMAN Yogyakarta.